2002
DOI: 10.1046/j.0016-8025.2001.00814.x
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic carbon assimilation and associated metabolism in relation to water deficits in higher plants

Abstract: SUMMARYExperimental studies on CO 2 assimilation of mesophytic C3 plants in relation to relative water content (RWC) are discussed. Decreasing RWC slows the actual rate of photosynthetic CO 2 assimilation (A) and decreases the potential rate (A pot ). Generally, as RWC falls from c . 100 to c. 75%, the stomatal conductance (g s ) decreases, and with it A. However, there are two general types of relation of A pot to RWC, which are called Type 1 and Type 2. Type 1 has two main phases. As RWC decreases from 100 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

62
1,006
6
68

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,613 publications
(1,142 citation statements)
references
References 106 publications
62
1,006
6
68
Order By: Relevance
“…This reduction in ATP synthesis is due to decreased electron transport and photophosphorylation caused by the loss of membrane-associated reactions. The membranes suffer structural damage because of the reduction in free water (LAWLOR & CORNIC, 2002). The results from the electrolyte leakage analysis (Table 1) indicated that the cellular membranes of leaves from conventional cultivars had significant more damage caused by water deficiency than those from the transgenic cultivars grown under the same water conditions.…”
Section: Resultsmentioning
confidence: 93%
“…This reduction in ATP synthesis is due to decreased electron transport and photophosphorylation caused by the loss of membrane-associated reactions. The membranes suffer structural damage because of the reduction in free water (LAWLOR & CORNIC, 2002). The results from the electrolyte leakage analysis (Table 1) indicated that the cellular membranes of leaves from conventional cultivars had significant more damage caused by water deficiency than those from the transgenic cultivars grown under the same water conditions.…”
Section: Resultsmentioning
confidence: 93%
“…At the first stage (42 DAS), plants were stressed for only two weeks and the water stress was mild, and thus no differences in photosynthetic related parameters were detected. However, the stress did have a negative impact on these parameters at 57 DAS (Figure 2) as expected [48,49].…”
Section: Impact Of Mild Drought Stressmentioning
confidence: 86%
“…When mild water deficits develop, stomatal closure is one of the first leaf responses, followed by a decline in P i and a downregulation of photosynthetic capacity to match the available carbon substrate (Brodribb, 1996;Chaves et al, 2002;Lawlor and Cornic, 2002). In both C 4 species grown at glacial pCO 2 , A declined alongside changes in g s , suggesting that stomatal closure had brought P i down to the steep initial slope of the A/P i curve, where C 4 photosynthesis becomes highly sensitive to changes in pCO 2 Gifford, 1995, 1996).…”
Section: Discussionmentioning
confidence: 99%